Photocatalytical Removal Of Lead Ions From Aqueous Solution With Immobilized Tio2 Powder On Carbon Based Plastic Plate In The Presence Of Calcium Oxalate And Thiolactic Acid [QD716.P45 V671 2005 f rb]. - Retnasamy, Vijenthi (2005)
Immobilized calcium oxalate followed by immobilized TiO2 on a carbon based PET (Polyethylene Terephthalate, PET) plastic plate was fabricated via electrophoretic deposition method.